Entities Issuing Securities Negotiable on the Stock Exchange - Vidal Ramírez, Fernando (1987)
The text analyzes the characteristics and regulation of entities issuing publicly traded securities in Peru, highlighting their importance within the financial market. It explains that these issues are reserved exclusively for legal entities, including public sector entities (state-owned companies under public, private and mixed law), as well as private sector corporations. In particular, the author points out that public companies generate share certificates that reflect their capital stock, while private companies use the public offering of shares as a mechanism to obtain financing and promote shareholding. In turn, publicly traded companies, characterized by their listing on the stock exchange, play a crucial role in mobilizing domestic savings and boosting the stock market. Next, it is commented that current legislation contemplates instruments such as convertible bonds and non-voting shares, which diversify financing alternatives. Finally, the need for a more robust regulatory framework to guarantee transparency and safeguard shareholders' interests is emphasized.